Increasing Fruit and Vegetable Intake Has No Dose-Response Effect on Conventional Cardiovascular Risk Factors in Overweight Adults at High Risk of Developing Cardiovascular Disease. Issue 7 (13th May 2015) - McEvoy, Claire T; Wallace, Ian R; Hamill, Lesley L; Hunter, Steven J; Neville, Charlotte E; Patterson, Christopher C; Woodside, Jayne V; Young, Ian S; McKinley, Michelle C
Abstract: Background: Improving diet and lifestyle is important for prevention of cardiovascular disease (CVD). Observational evidence suggests that increasing fruit and vegetable (FV) consumption may lower CVD risk, largely through modulation of established risk factors, but intervention data are required to fully elucidate the mechanisms by which FVs exert benefits on vascular health. Objective: The aim of this study was to examine the dose-response effect of FV intake on cardiovascular risk factors in adults at high CVD risk. Methods: This was a randomized controlled parallel group study involving overweight adults (BMI: >27 and ≤35 kg/m 2 ) with a habitually low FV intake (≤160 g/d) and a high total risk of developing CVD (estimated ≥20% over 10 y). After a 4-wk run-in period where FV intake was limited to <2 portions/d (<160 g/d), 92 eligible participants were randomly assigned to 1 of 3 groups: to consume either 2, 4, or 7 portions (equivalent to 160 g, 320 g, or 560 g, respectively) of FVs daily for 12 consecutive weeks. Fasting venous blood samples were collected at baseline (week 4) and post-intervention (week 16) for analysis of lipid fractions and high-sensitivity C-reactive protein (hsCRP) concentrations. Compliance with the FV intervention was determined with use of self-reported FV intake and biomarkers of micronutrient status. Ambulatory blood pressure and body composition were also measured pre- and post-intervention. Results: A total of 89 participants completed the study and body composition remained stable throughout the intervention period. Despite good compliance with the intervention, no significant difference was found between the FV groups for change in measures of ambulatory blood pressure, plasma lipids, or hsCRP concentrations. Conclusions: There was no evidence of a dose-response effect of FV intake on conventional CVD risk factors measured in overweight adults at high CVD risk. This trial was registered at clinicaltrials.gov as NCT00874341.